Ideologies, utopias and political culture - elements for understanding ideological dispute in Brazil in Coronavirus times (Simbiótica. Revista Eletrônica, 2020)
From the concepts of ideology and utopia in the perspective of Karl Mannheim’s Sociology of Knowledge, through its crystallization in long-term ideational complexes, such as Brazilian political culture, this article seeks to analyze the way the ideological dispute occurs in the contemporary Brazilian public debate in a scenario of sense crisis resulting from the coronavirus epidemic.Keywords: Ideologies; utopias; political culture; coronavirus.